2020
DOI: 10.1111/aje.12800
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of an introduced top predator (Felis catus) on a small African oceanic islet (Santa Luzia, Cabo Verde Islands)

Abstract: Studies on feral cat diet offer important ecological information and are the first step towards determining their impact upon endangered species. However, in comparing seasonal changes in diet with seasonal prey availability, the scarce amount of research into oceanic islands worldwide must be considered when deciding if a specific population is actually affected by cat predation. Cat diet was analysed on Santa Luzia (Cabo Verde Islands) since this invasive predator is considered one of the main threats to nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…For instance, in this study, we did not consider the impact that this rodent can have on vertebrates. However, we know that in Cabo Verde, mammal invaders already contributed to the extinction of endemic species (Mateo et al, 2005 ; Medina et al, 2021 ), therefore, it is important in the future to access the impact that M . musculus has on seabirds and terrestrial and marine reptiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in this study, we did not consider the impact that this rodent can have on vertebrates. However, we know that in Cabo Verde, mammal invaders already contributed to the extinction of endemic species (Mateo et al, 2005 ; Medina et al, 2021 ), therefore, it is important in the future to access the impact that M . musculus has on seabirds and terrestrial and marine reptiles.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in this study, we did not consider the impact that this rodent can have on vertebrates. However, we know that in Cabo Verde, mammal invaders already contributed to the extinction of endemic species (Mateo et al, 2005;Medina et al, 2021), therefore, it is important in the future to access the impact that M. musculus has on seabirds and terrestrial and marine reptiles. Further studies on other islands, particularly in Seychelles, show that the prevention, eradication, and control of rodents would very positively affect government revenues even after discounting the costs of such actions (Mwebaze et al, 2010).…”
Section: Stomach Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…This species was largely dependent on seabird colonies, feeding on eggs and chicks (Bocage 1896;Mateo 2012), and the disappearance of these seabird colonies may also have contributed to its extinction. Recently, Medina et al (2020) showed that on Santa Luzia, feral cats have also turned out to be a serious threat to reptiles, which represent more than 70% of their diet (in terms of consumed biomass).…”
Section: Discussionmentioning
confidence: 99%